Ka Po’ina Nalu1: a preliminary analysis of Peniche local surfers’ satisfaction concerning the surf tourism growth - Nunes, José Miguel (2022)
It is recognized that tourism is a sector that can contribute to the economic growth of a territory. Tourism produces social benefits to the region and positively contribute to the maintenance of a natural environment by protecting natural areas such as coastal areas, for example. On the other hand, the support of the local population is essential for the development, successful operation, and sustainability of tourism. In the case of surf tourism, achieving the goal of favorable community support for the tourism industry requires also an understanding of how local surfers formulate their attitudes toward tourism. Therefore, assessing residents’ satisfaction plays an important role in the management of a surf destination, particularly the satisfaction of the local surfers. The purpose of this study is to examine the satisfaction, among local surfers, regarding the growth of surf tourism, development model and territorial management of the municipality of Peniche, Portugal. This city is a well-known surfing destination, specifically since one of the stages of the world surf tour takes place on the beaches of this municipality. In order to achieve the objective of this study, surveys were applied to the local surfers community (n=119). The questionnaire consisted of three parts: the first focused on the surf practice; the second on the satisfaction level about the tourism growth and development model; and the third on the local surfer’s profile. The results of the survey carried out on the local surfers community have led to the conclusion that the data and information provided by this preliminary study will enable better governance and planning for the destination, looking to ensure the sustainability of the surf tourism in Peniche and, consequently, greater satisfaction for the local community and tourists.